2008
DOI: 10.1253/circj.72.67
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of Routine Primary Angioplasty in Patients Aged .GEQ.85 Years With Acute Myocardial Infarction

Abstract: follow-up. Conclusions The low incidence of procedural complications, together with good long term survival, suggest that primary PCI in STEMI patients ≥85 years is safe and efficacious, with a low rate of PCI failure in the presence of a low Killip class on admission, whereas primary PCI is unable to affect the poor prognosis for very old patients with cardiogenic shock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
24
3
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 11 publications
14
24
3
3
Order By: Relevance
“…22,23 In our study, very old STEMI patients also showed more marked inflammatory activation (as inferred by ESR and fibrinogen values), which may contribute to the increased glucose values; it is interesting to note that the infarct size (as inferred by Tn I values) was not significantly different among age groups. We further confirm that elderly STEMI patients show an increase inhospital mortality, 8,24 as well as increased values of NT-pro BNP. 25 It cannot be ruled out that the elevation of ESR in the older patients might be related to a possible higher prevalence of anaemia in these patients, which agrees with the observed decrease in the renal function.…”
Section: Discussionsupporting
confidence: 82%
“…22,23 In our study, very old STEMI patients also showed more marked inflammatory activation (as inferred by ESR and fibrinogen values), which may contribute to the increased glucose values; it is interesting to note that the infarct size (as inferred by Tn I values) was not significantly different among age groups. We further confirm that elderly STEMI patients show an increase inhospital mortality, 8,24 as well as increased values of NT-pro BNP. 25 It cannot be ruled out that the elevation of ESR in the older patients might be related to a possible higher prevalence of anaemia in these patients, which agrees with the observed decrease in the renal function.…”
Section: Discussionsupporting
confidence: 82%
“…This finding is in keeping with earlier clinical trials such as GISSI-2 and GUSTO-1 [9,10] as well as with previous studies in the era of mechanical revascularization by others [11][12][13][14][15][16] and us [17].…”
Section: Introductionsupporting
confidence: 91%
“…In fact, the elderly have a high prevalence of unrecognized and established diabetes [18] and diabetes is more common in the elderly patients with acute myocardial infarction (AMI) in respect to younger patients [17,[19][20][21]. In the Cooperative Cardiovascular Project (CCP), a nationally representative, community-based sample of elderly patients hospitalized with AMI [22], elevated glucose was common, rarely treated and associated with increased mortality, particularly in those without recognized diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Antoniucci et al 19 reported 16%, 30-day mortality rates in patients over 80 years old (mean age, 84 years) treated with primary PCI. Valente et al 20 reported a 17% in-hospital mortality rate in STEMI patients over 85 years old (mean age, 88 years) treated with PCI. They also found that age over 90 years as well as Killip class ≥ III on admission and PCI failure were independently correlated with in-hospital mortality.…”
mentioning
confidence: 99%